Analyzing the European institutional response to ethical and regulatory challenges of artificial intelligence in addressing discriminatory bias - Cerezo-Martínez, Pablo; Nicolás-Sánchez, Alejandro; Castro-Toledo, Francisco J. (Frontiers in Artificial Intelligence, 2024)
The European Union and some of its institutions have taken significant steps to address the challenges posed by the development and use of Artificial Intelligence (AI) in various contexts. The ubiquity of AI applications in everyday life, affecting both citizens and professionals, has made AI a common topic of discussion. However, as is evident from the documents analysed here, concerns have been raised about the possible negative social consequences of AI, in particular discriminatory bias, making it a particularly relevant issue if people-centred, rights-based AI is to be implemented. This article aims to examine the challenges of defining, identifying and mitigating discriminatory bias in AI systems from two perspectives: 1) to conduct an ethical and normative review of European Commission documents from the last 8 years (from GDPR to AI Act regulation); and 2) to expose recommendations for key stakeholders, including designers, end-users and public authorities, to minimise/mitigate this risk. The document review was carried out on 21 EU regulatory and ethical guidelines in the field of AI, from which 152 measures were extracted, differentiated between design, governance and organisational measures. It has also been observed that there is no clear conceptual framework on the issue at the European level, showing a clear problem in providing definitions of algorithmic bias and discrimination, but not in assessing their potential negative impact on individuals. Secondly, these gaps may affect the concreteness and detail of the possible mitigation/minimisation measures proposed and, subsequently, their application in different contexts. Finally, the last section of this paper presents a brief discussion and conclusions on possible issues related to the implementation of the measures extracted and certain limitations of the study.